Molecular Physical Properties of Cryogloblin in Patients with Hepatitis B Virus in Al-Najaf Province - Ahmed Aleiwi Al Hassani1 , Adil Ibadi AL-Luhaiby2, Mohammed Jasim Al-Shamarti1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cryoglobulins (CGs) are a cold precipitating abnormal immunoglobulins. The incidence of hepatitis B was discovered to be greater in age groups (46-55 years) relative to othe age groups. CGs were detected in 50 (33.3%) out of 150 patients with Hepatitis B. Three types of CGs precipitation nature were identified. Gelatinous (76%), flocculate (20%), and crystallineous (4%). No relation was found between patient’s age and CGs molecular physical properties. The cryocrit test of 50 serum samples revealed that CGs are characterized by their reversible precipitation at 4ºC between 12 hours to five days and solubility time at 37ºC ranged between half an hour and three hours.